Persistent SARS-COV-2 RNA positivity in a patient for 92 days after disease onset: A case report. Issue 34 (21st August 2020) - Wang, Junxue; Hang, Xiaofeng; Wei, Bo; Li, Dingchen; Chen, Fangyan; Liu, Wei; Yang, Chaojie; Miao, Xiaohui; Han, Li
Abstract: Rationale: Recently, patients with COVID-19 who showed persistently positive SARS-CoV-2 nucleic acid test results despite resolved clinical symptoms have attracted a lot of attention. We report the case of a patient with mild symptoms of coronavirus disease (COVID-19), who achieved clinical recovery but showed persistently positive SARS-CoV-2 nucleic acid test results until Day 92 after disease onset. Patient concerns: The patient is a 50-year-old man with mild symptoms of coronavirus disease (COVID-19). Diagnoses: COVID-19 pneumonia. Interventions: The patient was quarantined for 105 days. Of these, inpatient quarantine lasted for 75 days. When the nucleic acid test results were negative for 3 consecutive days, the patient was discharged at Day 75 after disease onset. During this period, multiple samples were collected from the patient's body surface, the surrounding environment, and physical surfaces, but none of these tested positive for SARS-CoV-2. These samples included those from anal swabs, hands, inner surface of mask, cell phone, bed rails, floor around the bed, and toilet bowl surface. However, nucleic acid retest results on Day 80 and Day 92 after disease onset were positive for SARS-CoV-2 nucleic acids. Outcomes: The patient continued with quarantine and observation at home. After the test results on Days 101 and 105 after disease onset were negative, quarantine was terminated at last. Lessons: Per our knowledge, this is the longest known time that a patient has tested positive for SARS-CoV-2 nucleic acids. No symptoms were observed during follow-up. During hospitalization, the SARS-CoV-2 nucleic acid positivity was not observed in samples from the body surface and surrounding environment, and no verified transmission event occurred during the quarantine at home. After undergoing clinical recovery a minority of patients with COVID-19 have shown long-term positive results for the presence of the SARS-CoV-2 nucleic acid. This has provided new understanding and research directions for coronavirus infection. Long-term follow-up and quarantine measures have been employed for such patients. Further studies are required to analyze potential infectivity in such patients and determine whether more effective antiviral drugs or regimens to enable these patients to completely clear viral infection should be researched.